Variability in Fodder Quality Traits of Anogeissus latifolia Wall. in Himachal Pradesh - Sankhyan, H. P.; Singh, N. B.; Bawa, R.; Gupta, Tanvi (Indian Forester, 2013)
Variability studies in fodder quality parameter in Anogeissus latifolia Wall (Family-Combretaceae) was undertaken in four districts of Himachal Pradesh viz., Solan, Sirmour, Kangra and Una at eight sites under different elevations in three diameter classes viz., 10-20 cm (small) 20-30 cm (medium) and 30-40 cm (Large). Proximate principles of leaf fodder in S4 (Chaoban, Distt Sirmour) and S1 (Jadli, Distt Solan) exhibited maximum variation in almost all nutritional traits. Study concluded indicating that direct selection from the altitude ranging between 600 m to 1000 m amsl in large diameter class (30-40 cm) is recommended for the improvement of species and to have superior genetic gains for further breeding works.